Review of external referrals to a regional stroke centre: it is not just about thrombectomy. Issue 12 (December 2019) - Adams, N.C.; Griffin, E.; Motyer, R.; Farrell, T.; Carmody, E.; O'Shea, A.; Murphy, B.; O'Hare, A.; Looby, S.; Power, S.; Brennan, P.; Doyle, K.M.; et al.
Abstract : AIMS: To determine the experience of a regional stroke referral centre of external referrals for endovascular thrombectomy (EVT) in patients with symptoms of acute ischaemic stroke (AIS) and large vessel occlusion (LVO). MATERIALS AND METHODS: Data were collected prospectively over two 4-month periods (2017–2018) on consecutive external referrals for EVT. Baseline demographics, imaging findings, and key time parameters were recorded. Reasons for not transferring patients and for not performing EVT were recorded. Key time intervals were calculated and compared between the transferred and non-transferred group with and without intracranial occlusion and between the transferred patients who underwent thrombectomy and those who did not. RESULTS: Two hundred and sixty-two patients were referred. Sixty-one percent ( n= 159) were accepted and transferred for treatment. Of those transferred, 86% ( n= 136) had EVT. Fourteen percent ( n= 23) were unsuitable for EVT on arrival due to no vessel occlusion (48% n= 11), poor Alberta Stroke Program Early CT Score (ASPECTS)/established infarct (30%, n= 7) haemorrhage (9%, n= 2), and clinical recovery (13% n= 3). One hundred and three patients (39%) were ineligible for EVT following phone discussion due to absence of intracranial occlusion (59%, n= 61), low ASPECTS (22%, n= 23), distal occlusion (4%, n= 4), low/improving National Institutes of Health Stroke Scale (NIHSS; 10.7%, n= 11), and poor modified Rankin Scale (mRS) at baseline (3%, n= 3). Patients with LVO but not transferred had longer onset to hospital arrival time compared with those transferred 151.5 versus 91 minutes ( p< 0.005), with a trend also toward a longer door to CT/CTA 40 minutes versus 30 minutes ( p= 0.142). CONCLUSION: These data provide valuable insights into the service provision of a comprehensive stroke network. The present rates of EVT and futile transfers are modest compared to published data. Access to neuroradiology and specialised stroke assessment is crucial to optimise time to treatment. Highlights: Evaluation of external referrals for thrombectomy to a comprehensive stroke centre. 52% of patients referred underwent thrombectomy. 22% of patients not eligible for thrombectomy due to established infarct. Significantly longer onset to hospital arrival time in those with LVO not transferred.